134k views
1 vote
43/(-12 + 22
( (2 x 3)2 + (-5 x 2 x 3) + 2
Give your answer in simplest form.

43/(-12 + 22 ( (2 x 3)2 + (-5 x 2 x 3) + 2 Give your answer in simplest form.-example-1
User Kismert
by
5.1k points

2 Answers

5 votes

Answer:

I think it is -1

Explanation:

Simplify the problem first.

Let's start with the numerator.

FYI, this, ^, means raised to the power of.

4^3 = 64

-12 + 2^2 = -12 +4 which equals -8

64/-8 = -8

Now simplify the denominator.

(2*3)^2 = 6^2 which equals 36.

-5*2*3 = -10*3 which equals -30

Then add the 2 to the end.

36 + (-30) + 2 = 6 + 2 which equals 8. This is the denominator.

Your fraction now is:

-8/8

Simplify this and you will get -1 as the simplest form.

Please forgive me if this is incorrect.

User Austin Downey
by
5.3k points
4 votes

9514 1404 393

Answer:

-1

Explanation:

A suitable calculator can find the value for you.


(4^3/(-12+2^2))/((2*3)^2+(-5*2*3)+2)=(64/(-12+4))/(6^2+(-5*2*3)+2)=(64/(-12+4))/(36+(-5*2*3)+2)\\\\=(64/(-8))/(36+(-30)+2)=(-8)/(6+2)=\boxed{-1}

43/(-12 + 22 ( (2 x 3)2 + (-5 x 2 x 3) + 2 Give your answer in simplest form.-example-1
User Novi
by
5.0k points